PENDAMPINGAN PENGELOLAAN PEMBELAJARAN DENGAN PENDEKATAN SAINTIFIK TK KEMALA BHAYANGKARI KABUPATEN BATANG HARI - Yennizar N Yennizar; Herwina Dewi Librianty; Novi Susanti (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2021)
Learning Management Assistance with a Scientific Approach at Kemala Bhayangkari Kindergarten, Batang Hari Regency. As mandated in Permendikbud No. 146 of 2014 concerning the curriculum for early childhood education, that learning management must be guided by the principles of learning, learning methods, and the character of early childhood. The learning approach used must be able to build scientific thinking in children through the 5 M process (observing, asking questions, gathering information, associating, and communicating). This activity aims to observe how the implementation of learning management in Kemala Bhayangkari Kindergarten as well as to assist Kemala Bhayangkari Kindergarten teachers in learning that focuses on implementing scientific thinking/scientific approaches in all children's activities. The limitations in this assistance are due to the time and available funds. The team's next hope is assistance for Kemala Bhayangkari Kindergarten in providing more varied experiences and play materials to fulfill children's freedom of play and fulfill the exploration of all their senses so that learning management is truly by the principles of learning, learning methods, and the character of early childhood.